2018
DOI: 10.3389/fphar.2018.01300
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cancer Pharmacological Treatments at the Turn of the Third Millennium

Abstract: The medical history of cancer began millennia ago. Historical findings of patients with cancer date back to ancient Egyptian and Greek civilizations, where this disease was predominantly treated with radical surgery and cautery that were often ineffective, leading to the death of patients. Over the centuries, important discoveries allowed to identify the biological and pathological features of tumors, without however contributing to the development of effective therapeutic approaches until the end of the 1800s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
418
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 709 publications
(468 citation statements)
references
References 246 publications
(247 reference statements)
0
418
0
9
Order By: Relevance
“…Cisplatin, carboplatin and oxaliplatin, the main platinum derivatives used in clinic, share similarities in their structure but also have differences in their mode of action (transport or DNA modifications for example) and are not used for the treatment of the same types of cancers (Table 1). CTR1 [58] ATP7B [60] Passive absorption [61] CTR1 [58,60] OCT1, OCT2 [60] Na + , K + -ATPase pump [60] MATEs [62] DNA Adducts Intra-strand and less frequently inter-strand connections [60] Fewer intra-strand and less frequently inter-strand connections than with cisplatin at equimolar concentrations [60,63] Intra and inter-strand connections more stable and inducing a more important DNA distortion [60] Repair Mechanisms NER and MMR [64,65] NER and MMR [65] NER [65] Type of Cancer Ovary, testis, bladder, colon, rectum, lung or head and neck cancers [66] Ovary, lung and ENT Reduced efficacy in testis, bladder and epidermoid head and neck cancers [67] Stage II/III colon cancers, metastatic colorectal cancers and NSCLCs [68] Side Effects Nausea, vomiting, nephrotoxicity, myelosuppression (thrombocytopenia, leucopenia, anemia) and peripheral sensory neuropathy (ototoxicity) [64] Less important neurotoxicity and ototoxicity than cisplatin Serious myelosuppression strong thrombocytopenia, neutropenia and anemia [60,66] Sensorial neuropathy but no hepatic or kidney toxicity [69] 3.1. Cisplatin…”
Section: Main Platinum Derivatives Used In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin, carboplatin and oxaliplatin, the main platinum derivatives used in clinic, share similarities in their structure but also have differences in their mode of action (transport or DNA modifications for example) and are not used for the treatment of the same types of cancers (Table 1). CTR1 [58] ATP7B [60] Passive absorption [61] CTR1 [58,60] OCT1, OCT2 [60] Na + , K + -ATPase pump [60] MATEs [62] DNA Adducts Intra-strand and less frequently inter-strand connections [60] Fewer intra-strand and less frequently inter-strand connections than with cisplatin at equimolar concentrations [60,63] Intra and inter-strand connections more stable and inducing a more important DNA distortion [60] Repair Mechanisms NER and MMR [64,65] NER and MMR [65] NER [65] Type of Cancer Ovary, testis, bladder, colon, rectum, lung or head and neck cancers [66] Ovary, lung and ENT Reduced efficacy in testis, bladder and epidermoid head and neck cancers [67] Stage II/III colon cancers, metastatic colorectal cancers and NSCLCs [68] Side Effects Nausea, vomiting, nephrotoxicity, myelosuppression (thrombocytopenia, leucopenia, anemia) and peripheral sensory neuropathy (ototoxicity) [64] Less important neurotoxicity and ototoxicity than cisplatin Serious myelosuppression strong thrombocytopenia, neutropenia and anemia [60,66] Sensorial neuropathy but no hepatic or kidney toxicity [69] 3.1. Cisplatin…”
Section: Main Platinum Derivatives Used In Cancer Treatmentmentioning
confidence: 99%
“…Ovary, testis, bladder, colon, rectum, lung or head and neck cancers [66] Ovary, lung and ENT Reduced efficacy in testis, bladder and epidermoid head and neck cancers [67] Stage II/III colon cancers, metastatic colorectal cancers and NSCLCs [68] Side Effects Nausea, vomiting, nephrotoxicity, myelosuppression (thrombocytopenia, leucopenia, anemia) and peripheral sensory neuropathy (ototoxicity) [64] Less important neurotoxicity and ototoxicity than cisplatin Serious myelosuppression strong thrombocytopenia, neutropenia and anemia [60,66] Sensorial neuropathy but no hepatic or kidney toxicity [69]…”
Section: Type Of Cancermentioning
confidence: 99%
“…The core epitopes (KMLLFSGRRLWRFDV) is thought to be the top binder as it interacts with 18 alleles; (HLA-DRB1*01:01,HLA-DRB1*03:01,HLA-DRB1*04:02,HLA-DRB1*07:01,HLA-DRB1*04:04,HLA-DRB1*08:01,HLA-DRB1*09:01,HLA-DRB1*13:01,HLA-DRB1*11:01,HLA-DRB1*13:02,HLA-DRB1*12:01,HLA-DRB1*15:01,HLA-DRB1*16:02,HLA-DRB3*01:01,HLA-DRB4*01:03,HLA-DRB5*01:01,HLA-DRB3*03:01,HLA-DRB4*01:01). Followed by (GRGKMLLFSGRRLWR, RGKMLLFSGRRLWRF,GKMLLFSGRRLWRFD,TFTRVYSRDADIVIQ, AVIDDAFARAFALWS,FARAFALWSAVTPLT,MLLFSGRRLWRFDVK, GNQLYLFKDGKYWRF, NQLYLFKDGKYWRFS) which binds to (17, 17, 18, 14, 14, 17, 15, 14, 14) alleles. (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Different type of immunotherapy are available including cytokine therapy, checkpoint inhibitors, monoclonal antibodies and therapeutic vaccines. (13, 14) With the latter being the center of many researches in the recent years, cumulating in the approving of Sipuleucel-T By the U.S. Food and Drug Administration (FDA) as the first dendritic cell based therapeutic vaccine for prostate cancer in 2010. (15, 16) vaccine can either be used alone or in combination with other modalities like immune checkpoint inhibitors (ICIs) which shows better results when compared with vaccine monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This observation led researchers to propose that actively dividing cancer cells may also be killed similarly by using such chemical compounds. Clinical data suggested that mustard gas suppress the division of cells of certain types of cancers such as leukemia and lymphomas (Falzone, Salomone, & Libra, 2018). For the past few decades, clinicians have emphasized to use a combinatorial approach to treat cancer where more than one anticancer drug is administered simultaneously and may be used as an adjuvant or neoadjuvant strategy (Cheng, Yang, & Shyur, 2016).…”
Section: Cancer Chemotherapymentioning
confidence: 99%